Derangements of immunological proteins in HIV-associated diffuse large B-cell lymphoma: the frequency and prognostic impact - Vaughan, Jenifer; Patel, Moosa; Suchard, Melinda; Gededzha, Maemu; Ranchod, Heena; Howard, Wayne; Snyman, Tracy; Wiggill, Tracey (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Diffuse large B-cell lymphoma (DLBCL) is an aggressive malignancy of B-cells frequently encountered among people living with HIV. Immunological abnormalities are common in immunocompetent individuals with DLBCL, and are often associated with poorer outcomes. Currently, data on derangements of immunological proteins, such as cytokines and acute phase reactants, and their impact on outcomes in HIV-associated DLBCL (HIV-DLBCL) is lacking. This study assessed the levels and prognostic relevance of interleukin (IL)-6, IL-10 and Transforming Growth Factor Beta (TGFβ), the acute phase proteins C-reactive protein (CRP) and ferritin; serum free light chains (SFLC) (elevation of which reflects a prolonged pro-inflammatory state); and the activity of the immunosuppressive enzyme Indoleamine 2,3-dioxygenase (IDO)in South African patients with DLBCL. Methods Seventy-six patients with incident DLBCL were enrolled, and peripheral blood IL-6, IL-10, TGFβ, SFLC and IDO-activity measured in selected patients. Additional clinical and laboratory findings (including ferritin and CRP) were recorded from the hospital records. Results Sixty-one (80.3%) of the included patients were people living with HIV (median CD4-count = 148 cells/ul), and survival rates were poor (12-month survival rate 30.0%). The majority of the immunological proteins, except for TGFβ and ferritin, were significantly higher among the people living with HIV. Elevation of IL-6, SFLC and IDO-activity were not associated with survival in HIV-DLBCL, while raised IL-10, CRP, ferritin and TGFβ were. On multivariate analysis, immunological proteins associated with survival independently from the International Prognostic Index (IPI) included TGFβ, ferritin and IL-10. Conclusion Derangements of immunological proteins are common in HIV-DLBCL, and have a differential association with survival compared to that reported elsewhere. Elevation of TGFβ, IL-10 and ferritin were associated with survival independently from the IPI. In view of the poor survival rates in this cohort, investigation of the directed targeting of these cytokines would be of interest in our setting.